Neurometabolic Hereditary Diseases of Adults (Springer International Publishing, 2018)
This practical book describes only neurometabolic hereditary diseases which have a specific treatment and encourages the general neurologist to think of the most common neurometabolic hereditary diseases, which he might have seen and never considered in the differential diagnosis. Information regarding how to deal with diseases with special therapy is provided (i.e. enzymatic replacement therapy in Fabry disease and Pompe disease), as is information on diseases which are not easily recognized (i.e. Niemann-Pick disease type C), and diseases with clinical features mimicking other common neurodegenrative diseases (i.e. Wilson's disease). Neurometabolic Hereditary Diseases is written with a clinical focus for adult neurologists working in general hospitals.